(untitled) (Research, Society and Development, 2023)
This study aimed to evaluate different intensity of irradiance and cytokinins concentration which can be influential in growth and volatile compounds production in vitro for Dysphania ambrosioides L., a plant present in the RENISUS list for medicinal plants with high interest in research and use. The irradiance intensities of 16.5, 36.6, 47.6 and 73.2 µmol m-2s-1 in the growth room were evaluated for nodal segments development. Three kinds of cytokinin (BAP, TDZ and Kinetin) in four different concentrations (0.0, 0.5, 1.0 and 2.0 mg L-1) were studied. Nodal segments were kept in growth room under 47.6 µmol m-2s-1 of irradiance and without cytokinin was found suitable for nodal segment growth in vitro. The number of volatile compounds of this species was not affected by irradiance intensity or cytokinin, however, the concentrations were affected.